The risk management dilemma for fumonisin mycotoxins - Shephard, G.S.; Kimanya, M.E.; Kpodo, K.A.; Gnonlonfin, G.J.B.; Gelderblom, W.C.A. (Elsevier, 2013)
Since the discovery of the fumonisins in 1988, extensive academic studies have generated much knowledge, including data on chemistry, biochemistry, toxicology, methods of analysis, natural occurrence in food supplies, fate during various processing procedures, and human and animal exposures. These mycotoxins have also been assessed by the International Agency for Research on Cancer (IARC) and have twice been the subject of risk assessments by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). The outcome of these investigations has been of a nature to alert risk managers to the necessity of controlling human exposure. However, the fumonisins occur mostly in maize, a world staple crop which is consumed in various communities at levels which can be as many as 100-fold different. Compounding the problem is the fact that maize is widely used as animal feed in many developed countries, whereas in Africa and some other developing countries, it is the primary food source. This contrast produces a problem for risk managers, partly solved at national level by the regulation of maximum tolerated levels (MTLs) applicable to individual countries. MTLs at an international level are currently under discussion at the Codex Committee on Contaminants in Food. The divergence in use and consumption and the fact that maize in various regions of the world can also vary greatly in contamination levels, leads to a dilemma for setting such MTLs, which would need to be low to protect the high maize consumers, but might then cause rejection of high amounts of the world supply. Higher MTLs, acceptable to maize exporters, would only protect the low maize consumers. This dilemma may only be solved by accepting that harmonizing regulations for raw maize is problematic and a more nuanced approach may be required.